G204(P) An unusually early presentation of pyloric stenosis. (24th May 2017) - Fordham, J; Kumar, Y; Doherty, L; Thorogood, S
Abstract : Aim: Describe a case of pyloric stenosis presenting within the first 24 hours after birth. Methods: Description of the case with images and review of the relevant literature. Results: A female baby, the first of dichorionic diamniotic twins, was born in good condition by Caesarian Section at 35 weeks gestation following spontaneous rupture of membranes. The pregnancy was otherwise uncomplicated and the mother had not been taking antibiotics. The baby was admitted to the neonatal unit at 10 hours of age with hypoglycaemia, vomiting and intermittent grunting. Examination was otherwise normal. A septic screen was performed and antibiotics commenced. Enteral feeds were limited and intravenous dextrose given because of bradycardic episodes noted whenever larger feeds were attempted. Bowels first opened at 25 hours and were regular until Day 6. By Day 9 there had been no further stools and large nasogastric aspirates and effortless milky vomits were still seen. Blood tests were largely unremarkable. Serial blood gases were normal. An abdominal x-ray performed on day 3 showed a large gastric bubble and non-specific bowel gas pattern. It was a barium meal study on day 9 that finally indicated the diagnosis, demonstrating no gastric emptying over a 25 min period. Immediately following this an abdominal ultrasound showed a hypertrophied pylorus (19 mm long and 4 mm thick). Pyloric stenosis of infancy is gastric outlet obstruction secondary to hypertrophy of the pylorus muscle. Incidence is reported as 1–8 per 1000 live births, with some studies finding it to be more common in first born children, in boys and in babies of Caucasian ethnicity. It normally presents between the third and eighth week of life 1 . Preterm babies tend to present later than term, though presentation in the first week of life is documented 2 . Conclusion: This case highlights the importance of considering investigation for pyloric stenosis irrespective of age and in the absence of metabolic alkalosis if enteral feeds are being witheld.